Home not Shelter! - Ein modularer Gemeinschaftsraum Ein prototypisches Realisierungsprojekt zur räumlichen Erweiterung von Gemeinschaftsunterkünften für Geflüchtete - Pasel, Ralf; Hacke, Max (CODE / architectural files, 2021)
The Home not Shelter! Plug-in is a usage-neutral room module that spatially expands the precarious living situation of refugees in emergency shelters and makes offers that go beyond mere accommodation. In the plug-in, refugees can get actively involved in a collaborative process and with professional support. The pavilion is to be planned in the immediate vicinity of existing refugee shelters and is adaptable in size. If necessary, it can change its location and be relocated to other workplaces. The "Home not Shelter! -Plug-in" can be an open space, event space and meeting place where new and old neighbors meet, exchange ideas and get to know each other. It can either be docked directly to the accommodation or set up in its vicinity. The plug-in has the potential to reproduce, expand, and multiply itself and to adapt to various locations and uses. The high aesthetic and architectural quality serves as a signal that 'refugee architecture' does not have to correspond to the precarious living situation of those affected.